Perception and degree of acceptance of menopause-related changes in various spheres of life by postmenopausal women - Dorota Robak-Chołubek; Artur Wdowiak; Marta Makara-Studzińska; Ewa Korczyńska (Annals of Agricultural and Environmental Medicine, 2014)
[b]Objective[/b]. The objective of the study was retrospective analysis of self-reported perception and acceptance of changes related to menopause among women 1–10 years after the occurrence of their last menstrual period. The selected aspects covered social contacts with the family level (social wellbeing), perception of own physicality and inner feelings concerning sex life (psychological wellbeing). [b]Materials and methods[/b]. The study covered 204 postmenopausal women 1–10 years after the last menstrual period. Analysis was performed based on a self-designed questionnaire and the data obtained were subjected to statistical analysis. Relationships were detected using the χ [sup]2[/sup] test. The p values p<0.05 were considered statistically significant (5% level of error probability). [b]Results[/b]. Women who coped with the menopausal transition easier more rarely perceived unfavourable changes in their family life. In the group of women with a high or very high level of difficulties in adaptation to menopause, the women twice less frequently declared positive sexual sensations or lack of changes. No significant differences were observed in the perception of own physicality and degree of experiencing the transition through menopause. [b]Conclusions[/b]. The perimenopausal period exerts a great effect on the psychological and social wellbeing of women. The degree of difficulties in experiencing the menopausal transition is important. Women who adapt to changes associated with menopause with more ease have fewer difficulties in their family life, and statistically less frequently report negative experiences in sexual contacts.